Factors influencing dietary tannin inclusion in dairy diets: A review - Lindokuhle Mhlongo; Cresswell Mseleku; Thando Tenza; Ignatius Nsahlai (Journal of Applied Veterinary Sciences, 2024)
T The objective of this paper was to evaluate factors affecting tannin dietary inclusion on enteric methane emission (CH4) and performance in dairy cows. Dairy production contributes to the greenhouse effect as it naturally emits enteric CH4. Therefore, this has sparked a need to control enteric methane emissions using anti-methane natural compounds such as tannins. Even at moderate dietary inclusions, tannin use in animal diets can occasionally reduce dairy performance and enteric CH4. This is due to the fact that most studies employ tannins to reduce enteric CH4 in dairy cows excluding other influential factors by focusing on the tannin inclusion effect alone. Therefore, there is a need to study different factors that influence the effect of tannins on enteric CH4 and dairy performance regardless of dietary tannin inclusion to improve the control of enteric CH4 at no expense to dairy performance. Hence, there is a need to identify factors that affect dietary tannin inclusion, such as tannin source, diet and animal factors that need consideration to prevent the control of enteric CH4 by tannins at the expense of animal performance. This approach would inform future studies relevant to the use of tannins in dairy diets to improve the effect of this treatment through in vivo and in vitro studies to ensure dairy production is harmless to the environment while meeting production targets.